A narrative review about cognitive impairment in Metabolic Dysfunction–Associated Steatotic Liver Disease (MASLD): Another matter to face through a holistic approach - Marica Meroni; Miriam Longo; Erika Paolini; Paola Dongiovanni (Journal of Advanced Research)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most common chronic hepatic disorder worldwide in both adults and children. It is well established that MASLD represents the hepatic manifestation of the metabolic syndrome whose definition includes the presence of obesity, type 2 diabetes (T2D), dyslipidemia, hypertension and hypercoagulability. All these conditions contribute to a chronic inflammatory status which may impact on blood brain barrier (BBB) integrity leading to an impaired function of central nervous system (CNS). Aim of review: Since the mechanisms underlying the brain-liver-gut axis derangement are still inconclusive, the present narrative review aims to make a roundup of the most recent studies regarding the cognitive decline in MASLD also highlighting possible therapeutic strategies to reach a holistic advantage for the patients. Key Scientific Concepts of Review: Due to its ever-growing prevalence, the MASLD-related mental dysfunction represents an enormous socio-economic burden since it largely impacts on the quality of life of patients as well as on their working productivity. Indeed, cognitive decline in MASLD translates in low concentration and processing speed, reduced memory, sleepiness but also anxiety and depression. Chronic systemic inflammation, hyperammonemia, genetic background and intestinal dysbiosis possibly contribute to the cognitive decline in MASLD patients. However, its diagnosis is still underestimated since the leading mechanisms are multi-faceted and unexplained and do not exist standardized diagnostic tools or cognitive test strategies. In this scenario, nutritional and lifestyle interventions as well as intestinal microbiota manipulation (probiotics, fecal transplantation) may represent new approaches to counteract mental impairment in these subjects.In sum, to face the “mental aspect” of this multifactorial disease which is almost unexplored, cognitive tools should be introduced in the management of MASLD patients.